2020
DOI: 10.1007/s11270-020-04781-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cultivable Bacteria Associated with the Root of Typha latifolia in a Constructed Wetland for the Removal of Diclofenac or Naproxen

Abstract: In this work, we designed at the level of microscale, subsurface flow wetlands planted with Typha latifolia, and used to remove diclofenac and naproxen from solutions that contained them. The wetlands were operated for 105 days with a hydraulic residence time (TRH) of 5 days. In these conditions, the removal efficiencies for diclofenac and naproxen were 98.4% and 97.7%, respectively. Moreover, we identified cultivable bacteria associated with the roots of plants exposed to either diclofenac or naproxen. We obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…The results showed that the wetland system planted with T. latifolia removed 82.0 % of diclofenac and 74.5 % of naproxen from the mixture. These results contrast with our previous work, where the removal efficiencies were 98.4 % for diclofenac and 97.7 % for naproxen in HSSF constructed wetlands planted with Typha latifolia and packed with gravel as support materials for plants; plants in the wetlands were exposed to single solutions of diclofenac (3 mg/L) or naproxen (5 mg/L) and the HRT was 5 days [17]. According to the results, diclofenac and naproxen were detected in the effluent, indicating that these substances were not completely removed as shown in Fig.…”
Section: Removal Efficiencies Of Diclofenac and Naproxen As A Mixture...contrasting
confidence: 99%
See 4 more Smart Citations
“…The results showed that the wetland system planted with T. latifolia removed 82.0 % of diclofenac and 74.5 % of naproxen from the mixture. These results contrast with our previous work, where the removal efficiencies were 98.4 % for diclofenac and 97.7 % for naproxen in HSSF constructed wetlands planted with Typha latifolia and packed with gravel as support materials for plants; plants in the wetlands were exposed to single solutions of diclofenac (3 mg/L) or naproxen (5 mg/L) and the HRT was 5 days [17]. According to the results, diclofenac and naproxen were detected in the effluent, indicating that these substances were not completely removed as shown in Fig.…”
Section: Removal Efficiencies Of Diclofenac and Naproxen As A Mixture...contrasting
confidence: 99%
“…Typha latifolia plants of 30 cm tall were planted in the HSSF-CW units and placed at intervals of 20 to 22 cm to allow the root development; the plants were grown for 90 days to achieve a vegetation coverage before experimentation according to that indicated by the U.S. Environmental Protection Agency [15]. During this period, the wetlands received a nutrient solution (1 mM NH4 + + 1.5 mM K + + 0.125 mM PO4 3− + 0.25 mM Ca 2+ ); in previous studies, this combination of nutrients favored the plant propagation and growth in greenhouse conditions, and in presence of diclofenac and naproxen, the plants did not show effects of damage such as chlorosis [16,17]. Two HSSF-CW units were planted with Typha latifolia, and the third one was unplanted.…”
Section: Experimental Installation and Operating Conditions Of The Ho...mentioning
confidence: 99%
See 3 more Smart Citations